INTERAKSI ANTARA PENDIDIKAN ISLAM DAN HUKUM ISLAM: MENANGGAPI TANTANGAN PEMINGGIRAN - Lizi Virma Surianti; Elpita Sari; Tamrin Kamal; Saifullah; Desi Asmaret; Julhadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the concepts of Islamic Education and Islamic Law, as well as their interrelation in addressing issues of marginalization in society. The problem addressed is how these two concepts can contribute to creating moral individuals and a just society, particularly for marginalized groups. The methodology used is a literature review, with data collected from various sources, including relevant books and articles. The findings indicate that Islamic Education serves as an empowerment tool that not only teaches academic knowledge but also shapes the character and morality of individuals. Islamic Law plays a crucial role in maintaining justice and protecting human rights, thereby addressing the social injustices faced by marginalized groups. The interconnection between Islamic Education and Islamic Law is essential in creating individuals capable of applying justice values in their daily lives.